PEGASO: a personalised and motivational ICT system to empower adolescents towards healthy lifestyles - Carrino, Stefano; Caon, Maurizio; Angelini, Leonardo; Mugellini, Elena; Abou Khaled, Omar; Orte, Silvia; Vargiu, Eloisa; Coulson, Neil S.; Serrano, José C.E.; Tabozzi, Sarah; Lafortuna, Claudio; Rizzo, Giovanna (IOS Press, 2014)
Unhealthy alimentary behaviours and physical inactivity habits are key risk factors for major non communicable diseases. Several researches demonstrate that juvenile obesity can lead to serious medical conditions, pathologies and have important psycho-social consequences. PEGASO is a multidisciplinary project aimed at promoting healthy lifestyles among teenagers through assistive technology. The core of this project is represented by the ICT system, which allows providing tailored interventions to the users through their smartphones in order to motivate them. The novelty of this approach consists of developing a Virtual Individual Model (VIM) for user characterization, which is based on physical, functional and behavioural parameters opportunely selected by experts. These parameters are digitised and updated thanks to the user monitoring through smartphone; data mining algorithms are applied for the detection of activity and nutrition habits and this information is used to provide personalised feedback. The user interface will be developed using gamified approaches and integrating serious games to effectively promote health literacy and facilitate behaviour change.